2019
DOI: 10.1016/j.eneco.2019.104475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of Australia's Small-scale Renewable Energy Scheme for rooftop solar

Abstract: Australia has among the highest rates of small-scale solar photovoltaic adoption in the world, with substantial geographical variation in uptake. Using postcode-level data up to December 2018, we quantify the impact of Australia's spatially-differentiated Small-scale Renewable Energy Scheme on solar uptake. We use spatial autoregressive models and other approaches such as a regression discontinuity design. The results indicate that postcodes receiving a higher subsidy factor have significantly more small-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 26 publications
0
16
1
5
Order By: Relevance
“…This highlights that non-targeted low-carbon incentives are likely to (re)produce social inequalities. In contrast to the present study, which showed a linear association of VEECs generation intensities and economic wealth of areas, the solar PV subsidy uptake was particularly high in postcode areas with middle-income households (Best et al 2019). Hence, it appears that varied mechanisms shape the uptake of the different types of low-carbon material home improvements.…”
Section: Low-carbon Gentrificationcontrasting
confidence: 99%
See 3 more Smart Citations
“…This highlights that non-targeted low-carbon incentives are likely to (re)produce social inequalities. In contrast to the present study, which showed a linear association of VEECs generation intensities and economic wealth of areas, the solar PV subsidy uptake was particularly high in postcode areas with middle-income households (Best et al 2019). Hence, it appears that varied mechanisms shape the uptake of the different types of low-carbon material home improvements.…”
Section: Low-carbon Gentrificationcontrasting
confidence: 99%
“…A sensitivity analysis was conducted to explore the VEECs generation intensity by households rather than dwellings. In contrast to other work that equated dwellings with households (Best et al 2019), this study worked on the premise that only occupied dwellings contained households, namely one household per occupied dwelling. More than 11% of dwellings in Victoria were unoccupied in the Census 2016 (ABS 2019a).…”
Section: Sensitivity Analysis Of Veecs Generation Intensity Per Housementioning
confidence: 99%
See 2 more Smart Citations
“…The RPS is assessed as the least suitable of the mechanisms at the present time in Vietnam, scoring poorly in terms of timeliness and institutional feasibility. While Australia's RPS shows that the approach certainly can work well (Best et al, 2019), it would take time for a well-functioning RPS to be established in Vietnam. A caution is that if a new FIT is set too high, it could trigger another solar PV investment rush, which could worsen short-term grid capacity concerns -in addition to overburdening EVN in terms of payments.…”
Section: Strategies For Further Adoption Of Solar Pvmentioning
confidence: 99%